2020
DOI: 10.1002/jcc.26183
|View full text |Cite
|
Sign up to set email alerts
|

Iodine substituted phosphorus corrole complexes as possible photosensitizers in photodynamic therapy: Insights from theory

Abstract: The search for new dyes to be used as photosensitizers in photodynamic therapy (PDT) is a field of great interest from both experimental and theoretical viewpoints.In this study, the main photophysical properties (excitation energies, singlet-triplet energy gap, and spin orbit coupling matrix elements) of some unsubstituted and iodine substituted phosphorus corrole complexes have been determined by using density functional theory and its time-dependent formulation. Results show that these compounds can be prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 41 publications
2
12
1
Order By: Relevance
“…On the other hand, the singlet oxygen quantum yields of the iodine-containing complexes 34 (60–71%) were higher than those observed for the non-iodinated complexes 32 (46–49%). These experimental results are in agreement with DFT and TDDFT computational calculations [ 47 , 48 ] performed with non-substituted and iodine substituted phosphorus corrole complexes. The results demonstrated that iodine-substituted phosphorus corrole complexes, such as 34 , are good candidates to act as photosensitizers in photodynamic therapy.…”
Section: Functionalization At the Inner Core And Peripheral Positisupporting
confidence: 88%
“…On the other hand, the singlet oxygen quantum yields of the iodine-containing complexes 34 (60–71%) were higher than those observed for the non-iodinated complexes 32 (46–49%). These experimental results are in agreement with DFT and TDDFT computational calculations [ 47 , 48 ] performed with non-substituted and iodine substituted phosphorus corrole complexes. The results demonstrated that iodine-substituted phosphorus corrole complexes, such as 34 , are good candidates to act as photosensitizers in photodynamic therapy.…”
Section: Functionalization At the Inner Core And Peripheral Positisupporting
confidence: 88%
“…This computational protocol, previously used 24–29 for the study of a series of PSs for PDT, was shown to be able to predict the structural and photophysical properties in agreement with the available experimental data.…”
Section: Computational Detailsmentioning
confidence: 69%
“…These properties can be reliably predicted by modern quantum chemical methods allowing a rational and a faster design of new PSs to be proposed for experimental verification and biological tests. Several works appeared in the literature in the last decade, showing that methods based on density functional theory (DFT) are able to provide valuable information on photophysical properties for a wide range of complex and medium‐large chemical systems 22–29 …”
Section: Introductionmentioning
confidence: 99%
“…The type II mechanism entails an energy transfer from the photosensitizer in its triplet state to molecular oxygen, promoting the formation of singlet oxygen, 1 O 2 . An efficient photosensitizer must possess a series of required chemical and photophysical properties, and some of them are of paramount importance: (i) a maximum absorption wavelength falling in the photodynamic therapeutic window (600-850 nm) to ensure a good penetration of light into living tissues [8,9]; (ii) a high intersystem spin crossing (ISC) probability between the excited singlet and triplet states; and (iii) a populated triplet state with an energy higher than 0.98 eV, the energy necessary to induce singlet oxygen formation from the ground triplet state [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%